Digital Transformation In Business Communication - Ashyfa Aulia Albina Rahman; Nayla Ayudhia Lestari; Mada Aditia Wardhana (TEKNOBIS : Jurnal Teknologi, Bisnis dan Pendidikan, 2026)
This study analyzes the impact of digital transformation on the financial performance of joint-stock commercial banks in Vietnam during the 2015–2021 period. Using text analysis of annual reports and a panel data approach with the System Generalized Method of Moments (System GMM), the study measures the level of digitalization through the frequency of technology-related keywords. The results indicate that the implementation of digital transformation has a negative effect on Return on Assets (ROA) and Return on Equity (ROE) in the short term, confirming the presence of a “profitability paradox” driven by high initial investment costs and infrastructure adaptation. Bank-specific factors such as the Non-Performing Loan (NPL) ratio weaken the positive impact of digitalization, while loan growth and Gross Domestic Product (GDP) growth act as positive moderating variables. The COVID-19 pandemic created a paradox by increasing profits through remote work efficiency, although digital cost pressures remained significant. The implications of this study highlight the importance of a structured digital roadmap, improvements in information technology infrastructure, and macroeconomic and credit risk management to support sustainable digital transformation.